Family relationships and personality traits of postural tachycardia syndrome - Matsui, Meiko; Yoshida, Seiji; Tanaka, Hidetaka; Yamawake, Ginroku; Kurooka, Yusuke; Ota, Yoshitaka; Kubo, Atsuko; Mizutani, Midori; Ashida, Akira (Frontiers in Pediatrics, 2025)
IntroductionOrthostatic intolerance is the name of the disease in Europe and the United States; however, in Japan, it is commonly known as orthostatic dysregulation (OD). OD is a physical disorder caused by failure of the body's compensatory regulatory mechanism to adapt to changes in circulatory dynamics during orthostasis; however, in many cases, the influence of psychosocial factors has been noted. The mother–child relationship is a major psychosocial factor in children, and it has been reported that parent–child patterns associated with OD are often excessive parental interference and child over-adaptation. This study focused on the psychological and physical factors of OD and assessed the parent–child relationship patterns among children with postural tachycardia syndrome (POTS), a subtype of OD, and examined how they relate to the child's personality traits and autonomic neuron function.MethodsA total of 36 six children diagnosed with POTS (mean age 13.5 ± 0.9 years) were compared with the results of the following questionnaires on parent–child relationships, personality traits, and the autonomic neuron function test: Family diagnostic test (a diagnostic test of parent–child relationship) for mothers and children, AN-EGOGRAM (the egograms that can be adapted to childhood and adolescence, when the ego is in the process of developing and growing), and a frequency analysis of heartrate and blood pressure variability for the children.ResultsAssessments of the mother–child relationship patterns among children with POTS found significant associations between maternal “strict discipline” and children's negative feelings, excessive parental intervention and children's susceptibility to stress, and the degree of children's “feeling of rejection” and lower supine vasomotor sympathetic nerve activity. The findings also suggested that children with POTS typically exhibited lower scores in critical parent and free child personality traits, but higher scores in adapted child (AC). Notably, mothers of children with high AC scores reported less dissatisfaction with their spouses regarding childcare.DiscussionIn the parent–child relationship in POTS, an association was observed between maternal “strict discipline” and children's negative feelings, suggesting that a less strict disciplinary approach may contribute to a more positive parent–child relationship.